Adipose Lipocalin 2 overexpression protects against age-related decline in thermogenic function of adipose tissue and metabolic deterioration - Jessica A. Deis; Hong Guo; Yingjie Wu; Chengyu Liu; David A. Bernlohr; Xiaoli Chen (Elsevier, 2019)
Objectives: Aging increases the risk for development of adipose tissue dysfunction, insulin resistance, dyslipidemia, and liver steatosis. Lipocalin 2 (Lcn2) deficient mice are more prone to diet-induced obesity and metabolic dysfunction, indicating a protective role for Lcn2 in younger mice. In this study, we determined whether overexpressing Lcn2 in adipose tissue can protect against age-related metabolic deterioration. Methods: We developed ap2-promoter-driven Lcn2 transgenic (Tg) mice and aged Lcn2 Tg mice for the metabolic assessments. Results: We found decreased adipocyte size in inguinal white adipose tissue (iWAT) from 10-month-old Lcn2 Tg mice relative to WT. This was accompanied by increased markers of adipogenesis in iWAT and attenuation of the age-related decline in AMP-activated protein kinase (AMPK) phosphorylation in adipose tissue depots. In addition to improvements in adipose tissue function, whole-body metabolic homeostasis was maintained in aged Lcn2 Tg mice. This included improved glucose tolerance and reduced serum triglycerides in older Lcn2 Tg mice relative to WT mice. Further, liver morphology and liver lipid levels were improved in older Lcn2 Tg mice, alongside a decrease in markers of liver inflammation and fibrosis. Conclusions: We demonstrate that overexpression of Lcn2 in adipose tissue not only preserves adipose tissue function during aging but also promotes maintenance of glucose tolerance, decreases dyslipidemia, and prevents liver lipid accumulation and steatosis. Keywords: Lipocalin 2, Adipose tissue, Adipose beiging, Healthspan